2006
DOI: 10.1590/s0100-40422006000400014
|View full text |Cite
|
Sign up to set email alerts
|

Incorporação de CuSO4 residual em argamassa, como método de disposição final

Abstract: Recebido em 14/4/05; aceito em 14/9/05; publicado na web em 16/2/06 INCORPORATION OF RESIDUAL CuSO 4 INTO CEMENT AS A FINAL DISPOSAL METHOD. Residual CuSO 4 was incorporated into the mass utilized for cement preparation. To a cement mass with 1:0.5:5 of cement, lime and sand to 0.25, 0.50, 0.75 and 1.00% of residual CuSO 4 were added. The sulfate was mixed separately with lime and water to induce metal precipitation. The hardened test bodies were submerged in Milli-Q water for three months. No Cu was detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…The study found that all mortars produced using M4 particles were classified as CS IV [32], and the hardening of cement was due to a chemical hydration reaction rather than drying. Various factors, such as the clinker quality, water/cement ratio, aggregate quality and content, and calcium hydroxide dosage, affect the mechanical strength of mortars [39]. Burning sludge at 900 • C enhances its pozzolanic activity, which involves binding lime in the presence of water to form insoluble calcium silicates [22].…”
Section: Sludge Ash (M4)mentioning
confidence: 99%
“…The study found that all mortars produced using M4 particles were classified as CS IV [32], and the hardening of cement was due to a chemical hydration reaction rather than drying. Various factors, such as the clinker quality, water/cement ratio, aggregate quality and content, and calcium hydroxide dosage, affect the mechanical strength of mortars [39]. Burning sludge at 900 • C enhances its pozzolanic activity, which involves binding lime in the presence of water to form insoluble calcium silicates [22].…”
Section: Sludge Ash (M4)mentioning
confidence: 99%